The Dietary Chitosan Positively Modulates the Growth and Survival of Barbonymus gonionotus Fry - Islam, F; Paul, SI; Das, TR; Barman, AK; Rahman, MA; Shaha, DC; Rahman, MM; Salam, MA (Annals of Bangladesh Agriculture, 2021)
The dietary chitosan has been largely used in the supplemental diets of terrestrial animals to improve growth and development. However, there is little information on the roles of dietary chitosan in growth and development of aquatic animals like fishes. Thus, this study aimed at determining the effects of dietary chitosan on growth performances and survival of Barbonymus gonionotus fry. A total of 600 B. gonionotus fry (2.12±0.02 g) were considered for this study. This experiment consisted of four treatments (0, 1, 2 and 3 g Kg-1 formulated feeds) and each treatment had three replications with a stocking density of 50 fry/tank. The dietary chitosan was supplied as 8% of body weight of each fry twice daily for 60 days. Fish fry treated with the dietary chitosan exhibited significant (P < 0.05) improvement in growth (body weight gain, % body weight gain, specific growth rate, and feed conversion ratio) and survival of B. gonionotus in comparison with untreated control. The water quality parameters, such as temperature, pH and dissolved oxygen showed no significant variations, and maintained suitable range throughout the study period for fish growth. Among the treatments, application of 1 g chitosan kg-1 feed showed the highest positive effects on growth and survival of B. gonionotus fry, indicating their potentials for practical application in promoting sustainable aquaculture. Ann. Bangladesh Agric. (2020) 24(1) : 41-50